Relationship of Birth Weight to Energy And Thiamin Consumption During the Last Trimester of Pregnancy - Fatin Fakhri Al-Deen Al-Talib; Maryam Mal-Alluha Al-Zubaydi (مجلة بغداد للعلوم, 2005)
the results pointed out that the average of energy amount obtained by the pregnant women was less than RDA so it amounted to 2014.4 keal/day which caused the birth weight to decrease to 2.8 kg which is less than the normal weight of a new-born child.